A BASIC REVIEW ON MICRO EMULSION AS A DRUG DELIVERY SYSTEM. - Saifi, Alfisha; Kapil Kumar; Deepak Teotia (Journal of Biomedical and Pharmaceutical Research, 2020)
Lipid dosage forms are attractive delivery systems for hydrophobic drug molecules. Emulsion is one of the popular system since many decades. Pharmaceutical applications of emulsions widened especially after micro emulsion emergence. Now a day Microemulsion is an emerging trade and having worldwide importance in a variety of technological applications. These applications include enhanced oil recovery, combustion, cosmetics, pharmaceuticals, agriculture, metal cutting, lubrication, food, enzymatic catalysis, organic and bio-organic reactions, chemical synthesis of nanoparticles etc. This review article deals with feature and application of microemulsion. a brief introduction and definition, structure, type, formation characteristics, stability, phase behavior and the effect of additives, pressure, temperature on the phase behavior of microemulsion . In addition to oral and intravenous delivery, they are amenable for sustained and targeted delivery through ophthalmic, dental, pulmonary, vaginal and topical routes. Microemulsions are experiencing a very active development as reflected by the numerous publications and patents being granted on these systems. They have been used to improve the oral bioavailability of various poorly soluble drugs including cyclosporine. Keywords: Microemulsion, Self micro emulsifying system, poor soluble, thermodynamically stable, Sustained & Controlled release, Drug delivery.